Diminished schwann cell repair responses play a role in delayed diabetes-associated wound healing - Zhou, Shaolong; Wan, Lingling; Liu, Xu; Hu, Delin; Lu, Feng; Chen, Xihang; Liang, Fangguo (Frontiers in Physiology, 2022)
Diabetes mellitus is the most common metabolic disease associated with impaired wound healing. Recently, Schwann cells (SCs), the glia of the peripheral nervous system, have been suggested to accelerate normal skin wound healing. However, the roles of SCs in diabetic wound healing are not fully understood. In this study, Full-thickness wounds were made in the dorsal skin of C57/B6 mice and db/db (diabetic) mice. Tissue samples were collected at different time points, and immunohistochemical and immunofluorescence analyses were performed to detect markers of de-differentiated SCs, including myelin basic protein, Sox 10, p75, c-Jun, and Ki67. In addition, in vitro experiments were performed using rat SC (RSC96) and murine fibroblast (L929) cell lines to examine the effects of high glucose conditions (50 mM) on the de-differentiation of SCs and the paracrine effects of SCs on myofibroblast formation. Here, we found that, compared with that in normal mice, wound healing was delayed and SCs failed to rapidly activate a repair program after skin wound injury in diabetic mice. Furthermore, we found that SCs from diabetic mice displayed functional impairments in cell de-differentiation, cell-cycle re-entry, and cell migration. In vitro, hyperglycemia impaired RSC 96 cell de-differentiation, cell-cycle re-entry, and cell migration, as well as their paracrine effects on myofibroblast formation, including the secretion of TGF-β and Timp1. These results suggest that delayed wound healing in diabetes is due in part to a diminished SC repair response and attenuated paracrine effects on myofibroblast formation.